A Construction of Activity Package on Creative Writing using Multimedia for Grade 8 students - Pongnirundorn, Areeyawat; Jongkonklang, Sirinat (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2023)
The objectives of this study entitled "A Construction of Activity Package on Creative Writing using Multimedia for Grade 8 students" which is a Experimental Research design, were: 1) to construct Learning activity package kit on creative writing using multimedia for Grade 8 students to meet efficiency criterion of 80/80 2) to study the students' creative writing abillity after using the activity package on creative writing using multimedia for Grade 8 students. The sample group used in this research consisted of 43 Grade 8 class 3 students studying in the first semester of the academic year 2020 at Nongkipittayakom School, Nongki, Buriram Province under Secondary Education Service Area Office 32, obtained by purposive sampling. Research tools used in the study were: 1) 6 activity packages on creative writing using multimedia for Grade 8 students 2) 6 lesson plans and 3) the creative writing ability test. Statistics used to analyze data included percentage, mean and standard deviation. Results of the study ware as follows; 1. 6 activity packages on creative writing using multimedia for Grade 8 students had the efficiency of process (E1) to the efficiency of product (E2) of 84.37/83.44 which was higher than the criterion of 80/80. 2. The score of the creative writing ability after using the activity package on creative writing using multimedia for Grade 8 students was 20.86 or 83.44% and S.D. = 1.71